Multispecies Alliances Against the Wasteocene: Counter-Narratives and Commoning Practices - Marco Armiero; David N. Pellow (Topoi)
ABSTRACT In this article, we will not engage with the scientific Anthropocene, rather, we are interested in challenging what Jason Moore has called the popular Anthropocene, that is, a narrative about the present socio-ecological crisis and its causes. The Wasteocene is part of a wider critique of the Anthropocene narrative that stresses the need to look at inequalities and power relationships to understand the socioecological crisis. Those alternative concepts are competing with the Anthropocene on a narrative ground; they are part of an imaginative mobilization to challenge the mainstream production and organization of collective narratives. This article is an apology for the power of narratives. Narratives can oppress, hide, or liberate. We will focus on stories of multispecies alliances against the Wasteocene; narratives are humans’tools. Though employing - actually celebrating - such an anthropocentric tool, we will go beyond the human, exploring the narratives that convey a sense of multispecies oppression and liberation.